Comparison of indices of ferokinetics, hemopoesis and IL-6 in children with bronchial asthma - Dudnyk, Veronika; Zhmurchuk, Vasyl (Journal of Education, Health and Sport, 2019)
Asthma is the most common chronic respiratory disease in children, the urgency of which is increasing with increasing incidence. The aim of the study. Conduct comparisons of ferrokinetics, hematopoiesis and interleukin - 6 in children with asthma. Materials and methods. According to our goal, we examined 144 children between the ages of 6 and 17 who have asthma.Results. In children with asthma who have a latent iron deficiency manifested by a decrease in ferritin <15 μg / l and a decrease in CST <20%, the risk of developing persistent moderate and severe disease is increased 1.5-fold.The risk of developing uncontrolled asthma increased in patients who experience a decrease in CST and an increase in the level of soluble transferrin receptors by 5.2 and 3.1 times, respectively.An increase in soluble transferrin/ferritin receptor levels above 1.5 causes a significant increase in the risk of developing uncontrolled asthma.In children with asthma with low serum iron, the rate of interleukin - 6 increased. In addition, a negative relationship between the transferrin saturation factor of iron and the content of interleukin - 6 in serum found to be of medium strength.